78.3k views
1 vote
3HELP__________________

3HELP__________________-example-1
3HELP__________________-example-1
3HELP__________________-example-2

1 Answer

3 votes

Answer:

m∠KIJ = m∠LIM ⇒ answer B

Explanation:

* Lets explain how to solve the problem

∵ I is the mid-point of NH

∴ IN = IH

- MJ is perpendicular to NH and passes through I the mid-point of NH

∴ MJ is perpendicular bisector of NH

- NH ⊥ MJ and intersects it at I

m∠NIM = m∠NIJ = 90°

- ∠ NIM consists of two angles ∠NIL and ∠MIL

∵ m∠NIM = m∠NIL + m∠MIL

- ∠NIJ consists of two angles ∠NIK and ∠JIK

∵ m∠NIJ = m∠NIK + m∠JIK

m∠NIL + m∠MIL = m∠NIK + m∠JIK ⇒ (1)

∵ NH bisects ∠KIL

m∠NIL = m∠NIK ⇒ (2)

- From (1) and (2)

∴ m∠MIL = m∠JIK

* m∠KIJ = m∠LIM

User Ira Herman
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.